Urinary Tract Desobstruction in Patients with Malignant Neoplasms of the Uterine Cervix - Nikolay Kolev; Alexander Vanov; Vladislav Dunev; Rumen Kotsev; Boyan Stoykov; Fahd Al-Shargabi (Journal of Biomedical & Clinical Research)
Cancer of the cervix causes internal, external compression or both of the upper urinary tract in 50-60%of patients in advanced stages. Retrograde stenting is the most widely used technique for desobstruction of the upper urinary tract in urology practice. Diversion of urine flow is an alternative, achieved by nephrostomy of one or both kidneys.We studied retrospectively 33 women with upper urinary tract obstruction caused by carcinoma of the uterine cervix operated on between March 2014 and March 2015 in the urology clinic at the University Hospital in Pleven, Bulgaria. Apercutaneous nephrostomy (PNS) was placed in 17 patients, and 11 patients hadaretrograde catheterization with ureteral stent type JJ. Five patients were treated with both methods. Placement ofa JJstent was the first choice procedure for all patients since it providesabetter quality of life. PNSimproves renal function faster than retrograde JJstenting. Therefore, the first method of choice for patients with an untreated primary cervical, uterine cancer is the placement of PNS. Retrograde JJstenting is the method of choice in patients who undergo surgery and radiation therapy withoutarelapse of the disease.